PSYCHODIAGNOSTIC METHODS IN MEDICINE - Nurbayeva Khabiba Batirovna; Aliyev Qamariddin Qakhramonovich; Eshmirzayev Quvonchbek Sodiq o’li (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
Psychodiagnostics in medicine is one of the key methods for assessing mental health, diagnosing psychiatric and neurological disorders. This article provides detailed information on the most essential psychodiagnostic methods.